Ideal Partner Criteria: Perspective of Islamic Youth in Makassar City - Wilda Ansar; Dian Novita Siswanti (Budapest International Research and Critics University, 2021)
Preference for choosing a ideal partner since adolescence is the beginning of an individual in determining whether his partner can be a partner to become the parent of his children. This study aims to find out the description of the criteria for a life partner in adolescence. The type of research used is descriptive quantitative. The data collection method used a survey method which was carried out by distributing online questionnaires. The number of respondents who filled out the questionnaire were 872 teenagers in Makassar and were Muslim consisting of 651 young women and 221 young men, with an age range of 14-19 years. The results showed that there were five factors that were used by adolescents as criteria in choosing a partner, namely partner characteristics, religion, occupation, physical appearance, and regional origin/domicile. Of the five factors, religion is the factor that has the largest percentage in choosing a partner, which is 78.5% and the lowest percentage factor is regional origin/domicile, which is 6.9%. When viewed from the gender aspect, adolescent girls and boys have different criteria in choosing a partner, namely male adolescents are more likely to choose a partner with the main criteria on physical appearance, while female adolescents state that the characteristics of a partner are the main factors in choosing a partner. The implication of this research is to provide knowledge and understanding regarding the determining factors in determining a life partner as well as an overview of the ideal partner expected by a teenager when entering domestic life. In addition, this study also has implications for premarital counselors in providing an overview of the differences in the criteria for the ideal partner expected by women and men.